Activation of FAK/Rac1/Cdc42‐GTPase signaling ameliorates impaired microglial migration response to Aβ42 in triggering receptor expressed on myeloid cells 2 loss‐of‐function murine models. Issue 8 (1st July 2020) - Rong, Zhouyi; Cheng, Baoying; Zhong, Li; Ye, Xiaowen; Li, Xin; Jia, Lin; Li, Yanfang; Shue, Francis; Wang, Na; Cheng, Yiyun; Huang, Xiaohua; Liu, Chia‐Chen; et al.
Abstract: Mutation of Triggering receptor expressed on myeloid cells 2 (TREM2) impairs the response of microglia to amyloid‐β (Aβ) pathology in Alzheimer's disease (AD), although the mechanism governing TREM2‐regulated microglia recruitment to Aβ plaques remains unresolved. Here, we confirm that TREM2 mutation attenuates microglial migration. Then, using Trem2 −/− mice and an R47H variant mouse model for AD generated for this study, we show that TREM2 deficiency or the AD‐associated R47H mutation results in inhibition of FAK and Rac1/Cdc42‐GTPase signaling critical for cell migration. Intriguingly, treatment with CN04, a Rac1/Cdc42‐GTPase activator, partially enhances microglial migration in response to oligomeric Aβ42 in Trem2 −/− or R47H microglia both in vitro and in vivo. Our study shows that the dysfunction of microglial migration in the AD‐associated TREM2 R47H variant is caused by FAK/Rac1/Cdc42 signaling disruption, and that activation of this signaling ameliorates impaired microglial migration response to Aβ42, suggesting a therapeutic target for R47H‐bearing patients with high risk of AD.